Pengaruh Green Innovation, Green Knowledege Management dan Green Transformational Leadership yang Dimediasi oleh Risiko terhadap Green Corporate Performance - Hendra Gunawan; Bahtiar Usman; Justine Tanuwijaya (CV. AFDIFAL MAJU BERKAH, 2025)
In the modern era and globalization that increasingly emphasizes the importance of sustainability, companies are required to adopt environmentally friendly business strategies to improve their competitiveness and performance. The concept of green corporate performance is one of the main indicators to measure the success of companies in implementing sustainability principles. This study examines general insurance companies, which have an important role in the financial sector and are strongly influenced by environmental factors and government regulations. The purpose of this study is to analysed the effect of green innovation, green knowledge management, and green transformational leadership on green corporate performance, with risk as a mediating variable. This research is expected to provide insight for management in formulating business strategies that are more sustainable and responsive to environmental challenges. The method used is a quantitative approach with statistical analysis to test the relationship between variables with 307 respondents. The results showed that green innovation has a direct influence on green corporate performance. Green innovation on risk has a direct influence. Green knowledge management has a direct effect on green corporate performance and green knowledge management has a direct effect on risk. Furthermore, green transformational leadership shows a direct influence on green corporate performance and green transformational leadership has a direct influence on risk. Risk has a direct influence on green corporate performance. In the mediation role analysis, it is found that green innovation mediated by risk has a partial mediation effect on green corporate performance. Green knowledge management mediated by risk has a partial mediation on green corporate performance. Green transformational leadership mediated by risk shows a partial mediation effect on green corporate performance. This finding indicates that although green innovation, green knowledge management, and green transformational leadership directly contribute to improving green corporate performance. The role of risk as a mediator also provides a partial influence (partial mediation) in strengthening the relationship. Therefore, general insurance companies need to pay attention to risk assessment and mitigation strategies in implementing green innovation, green knowledge management, and green transformational leadership to improve green corporate performance.